PENGARUH KARAKTERISTIK INDIVIDU DAN KOMUNIKASI INTERPERSONAL TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA PADA KOMITMEN ORGANISASI DINAS PERIKANAN KAMPAR - Fahrani Fauziah; Sri Indarti; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research is conducted in Dinas Perikanan Kabupaten Kampar and the purpose of this research is to determine the effect of Individual Characteristics and Interpersonal Communication to Job Satisfaction as well as its impact on Organizational Commitment to Dinas Perikanan Kabupaten Kampar. The population of this research is 71 people and the sample is taken by using census method which is making all the population as sample. The variables of this reseacrh are Individual Characteristics, Interpersonal Communication as independent variable and Job Satisfaction and Organizational Commitment as dependent variable. Data analysis method is descriptive analysis and multiple regression analysis of two stages by using program SPSS 22 for windows. The result of this research in the first stage that the individual characteristic and interpersonal communication partially and simultaneously have a significant effect on the job satisfaction and the second stage that the job satisfaction has significant effect to the organizational commitment. The coefficient of determination (R2) in the first stage is 0.512 which means the Characteristics of Individual and Interpersonal Communication can explain the Job Satisfaction variable equal to 51,2%, while the 48,8% is influenced by other variables not examined in this research. The The coefficient of determination (R2) in the second stage is 0,545 which means the Job Satisfaction can explain Organizational Commitment equal to 54,4%, while the 45,5% is influenced by other variable not examined in this research.Keywords : Individual Characteristic, Interpersonal Communication, Job Satisfaction, and Organizational Commitment.